Assessing the psychometric properties of the achievement goals questionnaire across task contexts - Muis, Krista R.; Winne, Philip H. (Canadian Journal of Education/Revue canadienne de l’éducation, 2012)
A program of research is necessary to examine the psychometric properties of instruments designed to measure individuals’ achievement goal orientations. Recently, research on achievement goal orientation has examined the stability of achievement goals to assess how context might influence individuals’ achievement goals. Accordingly, studies are necessary to establish factorial invariance across contexts. We examined the psychometric properties of the Achievement Goal Questionnaire (AGQ; Elliot & McGregor, 2001) across task contexts within a single classroom environment. We tested the factor structure by comparing five competing models and evaluated the invariance of the factor structure across four task contexts. Results revealed that the hypothesized four-factor structure was replicated, construct- and discriminantrelated evidence of validity were supported, and both internal consistency and test-retest reliability estimates were satisfactory. Moreover, invariance held at all levels across the various contexts. Keywords: Achievement goal orientation, measurement, factorial invariance, psychometrics, reliability.